Eine Konjektur zu Aischines Gegen Ktesiphon, 25 = A conjecture on Aeschines Against Ctesiphon, 25 - Futás, Nicolai; Hirsch, Tobias (Hermes, 2023)
In his oration Against Ctesiphon, Aeschines mentions the power his rival Demosthenes had during his term as treasurer of the theoric fund (ἐπὶ τὸ θεωρικόν). Many modern assumptions about the function of the Athenian financial administration and politics between the end of the Social War (357-355 BC) and the early 330’s BC are based on Aischin. Ctes. 25. This article argues for taking into account an emendation brought forward by the early 19. century British scholar Peter Paul Dobree. His suggestions, as will be shown, correspond better to the rhetorical structure of Aeschines’ argument than the prevailing reading and change the interpretation of the treasurers’ responsibilities.
Gesehen am 09.10.2023